Albumin In Situ Hybridization Can Be Positive in Adenocarcinomas and Other Tumors From Diverse Sites. Issue 2 (20th May 2019) - Nasir, Aqsa; Lehrke, Heidi D; Mounajjed, Taofic; Said, Samar; Zhang, Lizhi; Yasir, Saba; Shah, Sejal S; Chandan, Vishal S; Smyrk, Thomas C; Moreira, Roger K; Boland Froemming, Jennifer M; Herrera Hernandez, Loren P; et al.
ABSTRACT: Objectives: Albumin messenger RNA (mRNA) expression is a marker of hepatocellular differentiation. Most published data are from review of tissue microarrays, and albumin in situ hybridization (ISH) expression across several tumor types is incompletely characterized. Methods: Sections from 221 tumors were evaluated for albumin mRNA. Immunohistochemistry was used to confirm diagnoses. Albumin ISH was performed according to manufacturer-provided instructions. Fifty-nine cases were evaluated with both commercial ISH assays. Results: Albumin mRNA was detected in all hepatocellular carcinomas (HCCs) and 81% of intrahepatic cholangiocarcinomas. Lung (20%), gallbladder (39%), hepatoid pancreatic (n = 1 of 1) adenocarcinoma, breast invasive ductal carcinoma (18%), yolk sac tumor (25%), and acinar cell carcinoma (29%) showed expression. Both assays were concordant in 93% of cases. Conclusions: Albumin ISH was expressed in all HCCs studied. It was also positive in intrahepatic cholangiocarcinoma and patchy positive in gallbladder adenocarcinoma and a subset of other neoplasms, which can be a potential pitfall.